Development of Assessment to Measure Creative Thinking Skills of Junior High School Students on the Topic of Chemicals in Daily Life - Deka Putriani; Raden Gamal Tamrin Kusumah; Sukarno Sukarno (ISEJ : Indonesian Science Education Journal, 2023)
This study aims to develop an assessment instrument to measure junior high school students’ creative thinking skills in learning about chemical materials in daily life. The research employed the Borg and Gall research and development (R&D) model, adapted into eight stages: needs analysis, data collection, product design, expert validation, design revision, small-scale trial, product revision, and implementation trial. The study was limited to the small-scale trial phase. Validation instruments consisted of questionnaires administered to experts in assessment, subject matter, and language, as well as to one science teacher and 10 seventh-grade students. Data were analyzed using descriptive statistics by calculating the percentage of achievement in each component. Results indicated high validity: 87.69% (assessment expert), 95.5% (language expert), and 82% (material expert), categorized as “very feasible.” Student responses also showed high acceptance, ranging from 72% to 90% across components. These findings confirm that the developed assessment instrument is valid and feasible to be used as a learning tool in science education, with potential to enhance creative thinking in junior high school students.